Leadership-The Most Important Area of Educational Performance - Seema Bhakuni (Yayasan Ilomata, 2022)
Leadership is seen as the most critical aspect in successfully developing educational institutions, supporting stated aims and objectives, and enhancing education. It is a vital aspect in determining whether an organization succeeds or fails. A leader's style is defined by how he guides and encourages others to accomplish institutional objectives. Basic skills are described as